2017
DOI: 10.1080/1040841x.2017.1291578
|View full text |Cite
|
Sign up to set email alerts
|

The study ofH. pyloriputative candidate factors for single- and multi-component vaccine development

Abstract: Helicobacter pylori has grown to colonize inside the stomach of nearly half of the world's population, turning into the most prevalent infections in the universe. Medical care failures noticeably confirm the need for a vaccine to hinder or deal with H. pylori. This review is planned to discuss the most known factors as a vaccine candidate, including single (AhpC, BG, CagA, KatA, Fla, Hsp, HWC, Lpp, LPS, NAP, OMP, OMV, SOD, Tpx, Urease, VacA) and multi-component vaccines. Many promising results in the field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 155 publications
0
21
0
1
Order By: Relevance
“…Helicobacter pylori (H. pylori) is a common pathogenic bacterium worldwide including Iran. It is claimed to cause persistent gastrointestinal infection by colonization in the human gastric mucosa [1,2]. In the case of untreated and prolonged infection, H. pylori can cause peptic ulcer disease (PUD) and chronic gastritis (CG).…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) is a common pathogenic bacterium worldwide including Iran. It is claimed to cause persistent gastrointestinal infection by colonization in the human gastric mucosa [1,2]. In the case of untreated and prolonged infection, H. pylori can cause peptic ulcer disease (PUD) and chronic gastritis (CG).…”
Section: Introductionmentioning
confidence: 99%
“…CT, LT, synthetic oligodeoxynucleotides containing unmethylated CPG motif (CPG-ODN) have been proven efficient as adjuvants. Aluminum hydroxides (Alum) are the most common adjuvants utilized against H. pylori in studies, however their enhancement of cell immunity was insufficient (Eisenbarth et al, 2008;Mirzaei et al, 2017). In addition, novel potential adjuvant candidates have been explored, including chitosan and glycoprotein G (gG) from alpha herpes viruses (Gong et al, 2015;Walduck et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Urease, an important virulence factor and colonization factor for H. pylori , is the first H. pylori antigen that draw scientist's attention (5). Many studies have showed that urease might be a promising antigen for H. pylori vaccine (26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Urease (Ure) is considered to be an excellent candidate antigen for therapeutic vaccine against H. pylori (5). Several therapeutic subunit vaccines against urease have been developed, but no major breakthrough has been achieved (6, 7).…”
Section: Introductionmentioning
confidence: 99%